Impact of cystatin C-derived glomerular filtration rate in patients undergoing transcatheter aortic valve implantation - Kure, Yusuke; Okai, Tsukasa; Izumiya, Yasuhiro; Yoshida, Hisako; Mizutani, Kazuki; Yamaguchi, Tomohiro; Ogawa, Mana; Shibata, Atsushi; Ito, Asahiro; Takahashi, Yosuke; Shibata, Toshihiko; Fukuda, Daiju (Frontiers in Cardiovascular Medicine, 2023)
Background Chronic kidney disease (CKD) impacts prognosis in patients undergoing transcatheter aortic valve implantation (TAVI). While estimated glomerular filtration rate (eGFR) calculated from serum creatinine [eGFR (creatinine)] is affected by body muscle mass which reflects frailty, eGFR calculated from serum cystatin C [eGFR (cystatin C)] is independent of body composition, resulting in better renal function assessment. Methods This study included 390 consecutive patients with symptomatic severe aortic stenosis (AS) who underwent TAVI, and measured cystatin C-based eGFR at discharge. Patients were divided into two groups, with or without CKD estimated with eGFR (cystatin C). The primary endpoint of this study was the 3-year all-cause mortality after TAVI. Results The median patient age was 84 years, and 32.8% patients were men. Multivariate Cox regression analysis indicated that eGFR (cystatin C), diabetes mellitus, and liver disease were independently associated with 3-year all-cause mortality. In the receiver-operating characteristic (ROC) curve, the predictive value of eGFR (cystatin C) was significantly higher than that of eGFR (creatinine). Furthermore, Kaplan–Meier estimates revealed that 3-year all-cause mortality was higher in the CKD (cystatin C) group than that in the non-CKD (cystatin C) group with log-rank p = 0.009. In contrast, there was no significant difference between the CKD (creatinine) and non-CKD (creatinine) groups with log-rank p = 0.94. Conclusions eGFR (cystatin C) was associated with 3-year all-cause mortality in patients who underwent TAVI, and it was superior to eGFR (creatinine) as a prognostic biomarker.